PEMBUATAN PENYEDAP RASA INSTAN BERBAHAN DASAR TOMAT DENGAN PENAMBAHAN JAMUR TIRAM - Sidrat Samaun; Rosdiani Azis; Nur Fitrianti Bulotio (Program Studi Teknologi Hasil Pertanian, Politeknik Gorontalo, 2021)
Tomatoes have considerable potential. Tomatoes, both fresh and processed, have a fairly complete and good nutritional composition. Tomato fruit consists of 5-10% dry weight without water and 1 percent skin and seeds. People's habits in consuming foods such as vegetables and side dishes cannot be separated from the use of flavorings. Monosodium glutamate (MSG) is the sodium salt of glutamic acid which is a flavor compound and has been widely consumed by the whole world as a flavor enhancer, because the addition of MSG will make food more delicious. Glutamic acid can be obtained from natural ingredients such as tomatoes and mushrooms. The purpose of this research is to analyze water content, antioxidant activity, vitamin C and organoleptic for instant flavoring made from tomatoes and oyster mushrooms. The results of the organoleptic test using a discriminatory method on 35 panelists were able to distinguish tomato-based flavorings with comparison flavors before being added to instant noodles and after being added to instant noodles, both in terms of taste, color, aroma, texture, while for the results of chemical analysis, levels of water obtained an average value of 4.09% by using a drying time of 11 hours 30 minutes at a temperature of 60ºC, 9.7% antioxidant activity test showed the presence of antioxidant activity, and vitamin C test by titration method obtained an average value of 6.58% .